Teaching Object-Oriented Numerical Analysis - Rajan, S. D. (Journal of Engineering Education Transformations, 2016)
While a vast majority of engineers do not write computer programs for a living, every engineer working on any facet of their job responsibilities, deals with data and the means of extracting meaningful information from the data. The backbone of such analyses is formed by numerical methods. A very powerful engineering and scientific tool can be developed when numerical methods are combined with object-oriented techniques. The development of such a framework is discussed in this paper, and the implementation details are presented in the context of a senior undergraduate and graduate course where object-oriented programming via C++ is tied to numericalmethods such as the finite element analysis.